Comprehensive evaluation of the hot sweet soufflé dessert quality - Ditrikh, Iryna; Kuzmin, Oleg; Mikhailenko, Vladlena (My University, 2017)
The benefits of innovative hot sweet soufflé dessert in comparison with the prototype were established by methods of qualimetric and mathematical quality analysis. These methods have proved the expediency of using β-glucan in the recipe of dish to enhance nutrition value and to reduce the food energy value. Indicators of safety and microbiological indicators that are defined with the help of the Harrington’s scale of desirability have confirmed the safety of a new type of soufflé.
Keywords: солодкі страви; суфле; кваліметрія; якість; сладкие блюда; квалиметрия; качество; sweet dish; soufflé; qualimetry; quality; кафедра технології ресторанної і аюрведичної продукції